1983
DOI: 10.2307/1590379
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Pathogenesis of Staphylococcal Osteomyelitis in Chickens. I. Effect of Stress on Experimentally Induced Osteomyelitis

Abstract: A single strain of Staphylococcus aureus was used to study the pathogenesis of osteomyelitis in chickens. The disease was consistently reproduced in 6-week-old broiler chickens when 1 X 10(5) or more organisms were given intravenously. Severe feed restriction, debeaking, and single or multiple injections of corticosteroids delayed the appearance and decreased the severity of lesions due to staphylococcal infection. This increased resistance was associated with increased numbers of circulating heterophils and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 11 publications
3
28
0
Order By: Relevance
“…Interestingly, after intravenous inoculation of S. aureus to 29-day-old birds, lameness was generally observed after 2 days but birds could survive for up to a further 6 days . After intravenous inoculation of 26 groups of 45-day-old birds with S. aureus, Mutalib et al (1983a) found that clinical signs followed a similar pattern in all groups, with ruffled feathers, reluctance to walk, heads down, closed eyes, birds sitting on their hocks, and weak response to external stimuli. A sharp decrease in feed and water intake ensued, and death usually followed 2 to 5 days after the first appearance of signs (depending on the dose of inoculum).…”
Section: Clinical Signsmentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, after intravenous inoculation of S. aureus to 29-day-old birds, lameness was generally observed after 2 days but birds could survive for up to a further 6 days . After intravenous inoculation of 26 groups of 45-day-old birds with S. aureus, Mutalib et al (1983a) found that clinical signs followed a similar pattern in all groups, with ruffled feathers, reluctance to walk, heads down, closed eyes, birds sitting on their hocks, and weak response to external stimuli. A sharp decrease in feed and water intake ensued, and death usually followed 2 to 5 days after the first appearance of signs (depending on the dose of inoculum).…”
Section: Clinical Signsmentioning
confidence: 90%
“…Turkey osteomyelitis complex (TOC) is an important cause of lameness and of carcase condemnations in turkeys in the US (Bayyari et al, 1994). The pathogenesis of the condition in turkeys appears to be very similar to that in chickens, although TOC is associated with green livers in turkeys, but not in chickens (Mutalib et al, 1983a). Osteomyelitis caused by S. aureus is also a significant disease of children (Ish-Horowitz et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The lesions did not resemble primary bacterial osteomyelitis as described by Mutalib et al (1983), so the bacteria in the necrotic debris were probably secondary. Necrosis at the apex of dyschondroplastic cartilage in 4-to 5-week-old broiler chickens with tibial dyschondroplasia has been reported (Randall and Mills 1981) but is quite distinct from the lesions in the cases we have described.…”
Section: Fig 3 Proximal Tibiotarsus Showing Marked Lymphoid Hyperplmentioning
confidence: 69%
“…Macroscopic lesions in brain tissues following the injection of partridges were mostly inapparent, but the histopathological examination of the brain tissue revealed congestion and thrombosis. Experimentally induced staphylococcosis as well as naturally occurring disease have been reported in chickens (Mutalib et al 1983a, McNamee et al 2000, Jiang et al 2015, turkeys (Linares et al 2001, Corrand et al 2012, pet birds (Briscoe et al 2008, Huynh et al 2014, Iverson et al 2015, birds of prey (Poorbaghi et al 2012, Bezjian 2014, waterfowl (Degernes et al 2011, Mondal et al 2014, and other avian species (Lemon et al 2012). The pathogenesis of systemic infection with Staphylococcus aureus in chukar partridge chicks is not clearly defined.…”
Section: Discussionmentioning
confidence: 99%